Système d’aide pour la gestion des contrats en réassurances facultatives - Hassan, Henri; Pomerol, Jean-Charles; Sabroux, Camille (Assurances, 1995)
Decision support systems are now becoming standard equipment in the insurance business, such systems already provide valuable outcome in areas where expertise is standardized such as underwriting or evaluation of risks or damages. The matter is somewhat different in reinsurance since each contract happens to include specific characteristics, hence making the use of global tools unsatisfactory. Besides, the evolution of the reinsurance market requires the development of highly performing systems. This article introduces a support system assisting the decision making in facultative reinsurance. This project is two fold. (1) This system was originally developed as an expert system. When the information acquisition was completed for a prototype, it became obvious that, due to various factors such as the lack of information, multicriteria analysis or organization problems, it would be advisable to leave the responsibility for the system to the decision maker. (2) We have then designed an interactive multicriteria system intended to assist the decision maker in the selection of the facultatives according to five criteria and contextual information. In addition, this system will "memorize" various data allowing the appreciation of the quality of the selection and the follow up/anticipation of the market trends.